Nanofluidic terahertz metasensor for sensing in aqueous environment - Shih, Kailing (2019)
The terahertz spectral region has received tremendous attention for label free chemical and biological sensing, due to the presence of molecular fingerprints, low energy characteristics, and remote sensing capabilities. However, a major hindrance for the realization of a high performance terahertz bio-chemical sensor comes from the large absorption of terahertz waves by aqueous solution. Here, we overcome this limitation by confining the analyte-aqueous solution in a nanovolumetric fluidic chamber, integrated on metamaterial resonant cavities. The metamaterial resonators confine electromagnetic fields in extremely subwavelength space and hence allow for the enhanced interaction between the nanovolumetric analyte-aqueous solution and terahertz waves, while minimizing the absorption loss. We compare the sensing performance of split ring resonator and Fano resonator systems as metamaterial resonators. As a demonstration of chemical sensing, three alcoholic solutions with different concentrations were measured. Selective adenosine triphosphate (ATP) sensing capability was examined through ATP aptamer functionalization on gold metamaterials, where a decrease in the transmittance value was observed as the ATP concentration increased. The proposed sensing approach has the potential to be an effective tool for molecular analysis through exploiting the advantages offered by low energy terahertz, subwavelength metamaterial resonators and nanofluidic technologies.